Studi Ketimpangan Wilayah dan Potensi Ekonomi di Kabupaten Badung, Provinsi Bali - Ernah, Ernah; Afifah, Annisa Nashwa; Ananda, Vanya Dina; Nurhakim, Raihan Rizky; Rahma, Najwa Fauzia; Muhammad, Irfan (Universitas Galuh, 2025)
The success of regional development, especially Bali, is certainly an indicator of regional economic growth, which must be felt by all levels of society in the Province of Bali. This study aims to identify potential sectors that can be developed to encourage economic growth by classifying economic growth patterns in Badung Regency, as well as analyzing the level of regional inequality between Badung Regency and other regencies/cities in the Bali Province Area. The data collection method used is secondary data. The analysis used is Location Quotient (LQ) analysis, Klassen Typology, Shift-Share, Williamson Index, and Theil Index. The results of the analysis show that Badung Regency has a comparative advantage in 14 business sectors, in addition to the electricity and gas procurement sector, the transportation and warehousing sector, and the accommodation and food and beverage provision sector. Badung Regency has a lower economic growth rate but has a higher GRDP per capita compared to Bali Province, so it is included in one of the developed but depressed areas in Bali Province. Keywords: Regional inequality, Economic growth, Badung Regency, Shift-Share, LQ